PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE 2013-2018 - Rinofah, Risal; Cahyani, Elah Ria (Program Studi Manajemen, 2021)
This study aims to determine the effect of Current Ratio, Return On equity, Debt to Equity Ratio, dan Price Book Value on Stock Return. The population of this research is the food and beverage companies for the 2013-2018. Samples were taken using purposive sumping techniquie. The sample consisted of 11 companies from 16 food and beverage companies liested on the Indonesia Stock Exchange in 2013-2018, so the research data analyzed amounted to 60. Based on hypothesis testing using the t test, it is concluded that Current Ratio has a negative and significant effect on Stock Return, Return On Equity has a positive and significant effect on Stock Return, Debt to Equity Ratio has a negative and significant effect on Stock Return, Price Book Value has a significant negative effect.